"Be authentic: Be the most authentic 'you' you can be": Consejos from Latina administrative leaders in public higher education. Issue 1 (1st January 2023) - Velarde Pierce, Sharon
ABSTRACT: Despite the increasing entry of Latinas into higher education, this group continues to be underrepresented at the level of leadership. Previous studies have indicated Latinas that have achieved academic administrative leadership roles can play an important role in helping others to aspire to and attain such positions by offering guidance based on their own personal experiences and observations. However, to date, there have been limited efforts to collate and share that advice. Accordingly, drawing on conversations with Latina leaders in academia, this paper provides insight into the consejos that these leaders would offer others interested in pursuing leadership roles. The paper contributes to the growing literature on experiences of Latina leaders in higher education, while providing practical advice that will help Latinas to achieve a critical mass at the leadership level in US institutions of higher education.